Espécie nova de Euphyllodromia Shelford, 1908 do estado de Rondônia, Brasil e nova ocorrência de E. jugata Rehn, 1928 (Blattaria, Blattellidae) - Lopes, Sonia Maria; Oliveira, Edivar Heeren de; Araújo, Maria Carmosina de (Acta Amazonica, 2007)
Euphyllodromiarondonensis, sp. nov. is described from the Rondônia State, Brazil, based on the male genitalia. It's assinalated the new occurrence for E. jugata Rehn, 1928 from Acre State collected in wasps nest.", 'en
New species of Euphyllodromia Shelford, 1908 from Rondônia State, Brazil and new occurrence for E. jugata Rehn, 1928 (Blattaria, Blattellidae)
Keywords: Blattaria; E. Rondonensis Sp. Nov; E. Jugata, Rondônia; Taxonomy; Blattaria; E. Rondonensis Sp. Nov.; E. Jugata; Rondônia; Taxonomia